2021
DOI: 10.1038/s41541-021-00372-x
|View full text |Cite
|
Sign up to set email alerts
|

Subclass and avidity of circumsporozoite protein specific antibodies associate with protection status against malaria infection

Abstract: RTS,S/AS01 is an advanced pre-erythrocytic malaria vaccine candidate with demonstrated vaccine efficacy up to 86.7% in controlled human malaria infection (CHMI) studies; however, reproducible immune correlates of protection (CoP) are elusive. To identify candidates of humoral correlates of vaccine mediated protection, we measured antibody magnitude, subclass, and avidity for Plasmodium falciparum (Pf) circumsporozoite protein (CSP) by multiplex assays in two CHMI studies with varying RTS,S/AS01B vaccine dose a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…The junctional epitope appears to be a highly susceptible target for inhibitory antibodies 16 , 17 , 22 , as evidenced by sterilizing protection observed in humans following mAb CIS43 passive transfer 64 . However, RTS,S (which lacks the junctional region) antibodies also bind to the junctional region 65 , and it has been suggested that junctional binding was a result of affinity maturation of (NPNA) n -specific antibodies 21 , 66 . To our knowledge, there has been no direct comparison of vaccines displaying the junctional and the major repeat region of CSP.…”
Section: Discussionmentioning
confidence: 99%
“…The junctional epitope appears to be a highly susceptible target for inhibitory antibodies 16 , 17 , 22 , as evidenced by sterilizing protection observed in humans following mAb CIS43 passive transfer 64 . However, RTS,S (which lacks the junctional region) antibodies also bind to the junctional region 65 , and it has been suggested that junctional binding was a result of affinity maturation of (NPNA) n -specific antibodies 21 , 66 . To our knowledge, there has been no direct comparison of vaccines displaying the junctional and the major repeat region of CSP.…”
Section: Discussionmentioning
confidence: 99%
“…In studies following RTS,S/AS01E vaccination outcomes, it was hypothesized that antibody subclass and avidity measurements combined with specificity would associate with protection status. Protective immunity was mostly associated with the cytophilic subclasses (IgG1 and IgG3 in humans, IgG2 in mice) and multiple repeating sequences present in RTS,S formulation were considered to enhance the avidity of the antibodies ( 35 ). Also, a correlation of protective immunity was suggested to more prolonged antigen exposure, facilitating response to pre-erythrocytic antigens ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…This fact may indicate that the differentiation of Plasma Cells is favored in Montanide-adjuvanted mice. This point deserves special attention since it was demonstrated that RTS,S vaccine-elicited CSP-specific antibody titers are associated with protection and with enhanced expression of genes related to differentiation of Plasma Cells ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…The potency of anti-PfCSP antibodies may also be affected by their isotype or subclass and associated effector function, e.g., via complement fixation and interactions with Fc receptors mediating phagocytosis or parasite killing by NK cell activation ( Leitner et al, 2020 ). Numerous serological studies investigated the link of these antibody properties to protection ( Suscovich et al, 2020 ; Seaton et al, 2021 ; Young et al, 2021 ). However, the polyclonal composition of serum antibodies, the fact that antibody specificity and effector function are directly linked, and differences in assay setups across studies complicate these analyses.…”
Section: Specificity Quality and Function Of Anti-pfcsp Antibodiesmentioning
confidence: 99%